Detection of pap-, sfa- and afa-specific DNA sequences in Escherichia coli strains isolated from extraintestinal material - Bogyiová, E; Kmetová, M; Biros, E; Siegfried, L (Folia microbiologica, 2002)
P-fimbriae, S-fimbriae and AFA-adhesins are virulence factors responsible for adherence of Escherichia coli strains to extraintestinal host-cell surface. Detection of pap-, sfa- and afa-specific sequences performed by PCR revealed 74% pap+, 65% sfa+, and 8.3% afa+ strains in a group of 84 extraintestinal E. coli isolates. Detection in a group of fecal strains showed 29% pap+, 21% sfa+ and 4% afa+ strains. pap together with sfa were found as the most frequent combination (56%) among extraintestinal isolates probably due to localization of pap- and sfa-operons on a common pathogenicity island. The occurrence of afa-specific sequence among 56 urine strains was 11%, although no afa+ strain was detected among 28 gynecological isolates. No strains with detected adhesin operons were found among twenty (24%) extraintestinal E. coli strains.
Keywords: infekce vyvolané Escherichia coli; Escherichia coli Infections; cystitida; DNA bakterií; Infant; Humans; Adhesins, Escherichia coli; kojenec; lidé středního věku; dítě; Pyelonephritis; Child; Female; Fimbriae, Bacterial; dospělí; Virulence; Escherichia coli; lidé; virulence; Bacterial Adhesion; gynekologická onemocnění; Genital Diseases, Female; předškolní dítě; Adult; DNA, Bacterial; bakteriální adheze; adheziny Escherichia coli; ženské pohlaví; Middle Aged; Cystitis; polymerázová řetězová reakce; Polymerase Chain Reaction; pyelonefritida; bakteriální fimbrie; Child, Preschool